The Green Paradox and the Choice of Capacity - Markus Zimmer; Marc Gronwald; Darko Jus (Verein für Socialpolitik, 2010)
A number of recent papers extend traditional Hotelling frameworks by the topical issue of climate change. They study the effects of different environmental taxes on the resource extraction paths and derive important and far-reaching policy implications. In particular the most recent strain of literature devoted to the so called Green Paradox shows how over various economic channels a steady increase in environmental taxation rather accelerates resource extraction instead of resulting in the desired slow down. The cause of this paradox lies in the inability to tax the supply side of the resource and thus limits the policy instruments to the demand. Thus, e.g. an oil-sheikh has an interest to sell his oil while it is still relatively low taxed and he can still generate higher profits. This effect could be seen as a kind of intertemporal carbon leakage transferring future extraction to the present. The Green Paradox literature generally concludes that a binding global certifcate system covering all CO2 sources is the only solution and that attempts of implementing greener policies in the transition process are counterproductive. However, the underlying implicit assumption is that extraction capacities are suffcient and that capacity adjustments are costless. Our paper accounts for an endogenous capacity building decision under convex adjustment costs by extending the original Hotelling type formulation of the Green Paradox. The analysis shows that for typical assumptions about the cost structure greener policies stay a useable instrument in the transition process. We are able to define the necessary conditions for the policy measures to be effective and show that the evaluation of the Green Paradox differs for pre and post oil-peak regimes.
Keywords: Q50; C61; Q31; 330; Global warming; carbon taxation; optimal taxation